2016
DOI: 10.1051/0004-6361/201526895
|View full text |Cite
|
Sign up to set email alerts
|

Abundances of carbon-enhanced metal-poor stars as constraints on their formation

Abstract: Context. An increasing fraction of carbon-enhanced metal-poor (CEMP) stars is found as their iron abundance, [Fe/H], decreases below [Fe/H] = −2.0. The CEMP-s stars have the highest absolute carbon abundances, [C/H], and are thought to owe their enrichment in carbon and the slow neutron-capture (s-process) elements to mass transfer from a former asymptotic giant branch (AGB) binary companion. The most Fe-poor CEMP stars are normally single, exhibit somewhat lower [C/H] than CEMP-s stars, but show no s-process … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
68
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 96 publications
(169 reference statements)
5
68
4
Order By: Relevance
“…We refer to these chemically peculiar stars as carbon-enhanced metal-poor (CEMP) stars. Slightly different definitions of CEMP stars have been proposed (see for example Hansen et al 2016, and references therein), but we prefer to keep the "classical" definition, for the reasons explained in Bonifacio et al (2015). As CEMP stars make up a considerable fraction of metal-poor stars, it is important to understand how they acquired their enhanced carbon abundance.…”
Section: Introductionmentioning
confidence: 99%
“…We refer to these chemically peculiar stars as carbon-enhanced metal-poor (CEMP) stars. Slightly different definitions of CEMP stars have been proposed (see for example Hansen et al 2016, and references therein), but we prefer to keep the "classical" definition, for the reasons explained in Bonifacio et al (2015). As CEMP stars make up a considerable fraction of metal-poor stars, it is important to understand how they acquired their enhanced carbon abundance.…”
Section: Introductionmentioning
confidence: 99%
“…The latter scenario is more likely as a result of the instability of the Roche lobe in thermally pulsing AGB stars and the typically larger spatial separations of these binary systems (Paczyński 1965, Abate et al 2013. Similarly, Herwig (2005), Placco et al (2013), and Hansen et al (2016c) have shown the abundance profiles of the CEMP-s stars are consistent with enrichment from an AGB companion. The difference between these similarly natured objects currently exists only in an arbitrary cut in metallicity.…”
Section: Introductionmentioning
confidence: 93%
“…ALW-8 is in the RGB phase where the primordial carbon abundance has been reduced due to the CN cycling and the presently observed abundance will be lower. While the moderate [C/N] ratio of −0.2 dex alone would suggest that its surface composition has not been significantly altered by internal mixing during stellar evolution (Spite et al 2005;Hansen et al 2016a), other tracers of mixing paint a different picture. Amongst these are the strong depletion in lithium and the carbon isotopic ratio, where Spite et al (2006) suggest an upper limit of 12 C/ 13 C < 10 as a proxy for effective deep mixing.…”
Section: Origin Of Carbonmentioning
confidence: 99%
“…Amongst these, Carbon-enhanced metal-poor (CEMP) stars (defined by [Fe/H] < −2.0 and [C/Fe] >0.7) are of great interest since the origin of the carbon overabundance is versatile and closely related to the formation and enrichment history of the Send offprint requests to: A. Susmitha; e-mail: susmitha@iiap.res.in; a.koch1@lancaster.ac.uk; sivarani@iiap.res.in Based on observations collected at the European Southern Observatory at Paranal, Chile; Large Programme proposal 171.B-0520. Table A.1 is available in electronic form at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsweb.ustrasbg.fr/cgi-bin/qcat?J/A+A/ host stellar system (Aoki et al 2007;Masseron et al 2010;Carollo et al 2014;Bonifacio et al 2015;Hansen et al 2016a;Koch et al 2016;Lee et al 2017). These stars are primarily categorized based on the presence and absence of neutron capture elements as CEMP-s, CEMP-r, or CEMP-r/s, versus CEMP-no, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation